Synopsis: Cost and policy determinants of features of tractor markets in Nigeria: Case studies of tractor sellers in Kaduna state and tractor owners in Benue state - Hatzenbuehler, Patrick L.; Takeshima, Hiroyuki; Edeh, Hyacinth O.; Lawal, Akeem (International Food Policy Research Institute, 2018)
There is a need to undertake more thorough assessments of relevant agricultural machinery markets to determine why machine usage by farmers is potentially lower than it would be under ideal market conditions. Our study focuses on four-wheel tractors. Information and data on tractor market structure, conduct, and performance in Africa is sparse. To partly fill this gap, we implemented a qualitative review of two tractor markets in Nigeria – survey-based assessments of the business characteristics of tractor sellers in Kaduna state and of tractor owners in Benue state. Detailed characterizations of the vertical and geographic distribution of these businesses and identification of principal revenue sources and costs were obtained through the surveys.